Occupational Exposure to formaldehyde in pathology laboratories - Pires, Ana Filipa (2019)
Occupational exposure to formaldehyde by inhalation causes irritation of the mucous membranes of the eye and upper respiratory tract (nose and throat), leading to tingling, redness or burns to the nose and throat, nasal discharge and watery eyes. At concentrations below 1 ppm symptoms are usually negligible, but they become disturbing when concentrations exceed 2 to 3 ppm. According to IARC, continuous occupational exposure to formaldehyde causes cancer of the nasopharynx and leukemia. IARC classified formaldehyde in group 1 (carcinogenic to humans) in 2004. Formaldehyde is used worldwide, mainly in the production of resins and adhesives used in wood, paper, plastic and textile industry. It is also used in aqueous solutions as a disinfectant and preservative in embalming activities and pathology laboratories. Pathology laboratories receive organ, tissue, or cell specimens collected from humans to study their structural alterations and to serve as support in the diagnosis and prognosis. The main steps are the preparation of formaldehyde solutions, macroscopy, placing the samples in cassettes and microscopic observation. Supporting tasks, necessary to laboratory operation, are emptying and maintenance of the parts prepared, elimination of specimens, recycling or elimination of the waste formaldehyde solutions. Based on results obtained in routine exposure evaluations, formaldehyde concentrations in Portuguese pathology laboratories are not always negligible, so it is important to share them in order to raise awareness to the problem.